PERANCANGAN MEJA LAPTOP PORTABEL MENGGUNAKAN METODE RAPID UPPER LIMP ASSESSMENT (RULA) DAN PENDEKATAN ANTROPOMETRI - Iksan Adiasa; Ryan Suarantalla (Program Studi Teknik Industri, Fakultas Rekayasa Sistem, 2020)
The use of computers or laptops is carried out in almost all levels of education. Activityroutine in front of laptops that are used for long periods of time can causehealth problems such as musculoskeletal injuries and Carpal Tunnel Syndrome (CTS).In preventing these problems, it is necessary to design a tool in the form oflaptop table that conforms to the human body or anthopometry. The design is carried outby analyzing work posture using the RULA method. User work postureThe observed laptop is the working posture for the angle of the body posture of an object. The work posture isthere is today the use of laptops without desks and using common desks, showsThe result is that repairs need to be done immediately, while the presence of a laptop tableportable, table results in a lower and better work posture. Expectedby making this portable laptop table the risk of musculoskeletal injury and the Carpal TunnelSyndrome (CTS) can be reduced